Language Etiquette and Culture in Teaching of Foreign Languages. In: Journal “Practice and Theory in Systems of Education (P.T.S.E.)” ISSN 1788-2591 (Online), ISSN 1788-2583 (Printed) Vol. 5, Number 3 2010, Budapest, Hungary. pp. 205-218. - Csajbok-Twerefou, I. (My University, 2010)
Most of the time people learn foreign languages for communication – to be able to speak and understand. In the early stages of the teaching of any foreign language, teachers introduce language etiquette of the studied language for better understanding and appreciation of aspects of the culture. This is partly due to the fact in many cases language learning starts from “Hello”, or “My name is…” etc., and also there are major differences between the studied and native languages which describe these languages and their speakers. This indicates that language etiquette should be a part of any language teaching and learning process. The learning of foreign languages at any level is characterized by the interplay of many factors such as mother tongue, culture, educational background, psychological factors, among others. A difficult task that faces an instructor is the development of the socio-cultural competence in teaching a foreign language. In the University of Ghana, students have the opportunity to study Russian language and literature as part of the course content. This paper discusses some challenges in the teaching Russian language in the University of Ghana. Analysis shows that irrespective of the fact, that many Ghanaians speak one other Ghanaian language in addition to their mother tongue, and English which is the official language, and some people also speak French, there is a major challenge in teaching Russian in Ghana as a foreign language. Thus, multilingualism is a useful but not sufficient condition for the effective learning of a language. The paper argues that one reason that makes it difficult to teach Russian as a foreign language is the social and cultural differences and the wide geographical distance between Ghana and Russia.
Keywords: language etiquette; foreign languages; language teaching; culture; politeness